Categorization of General Problems and Defects in Historical Building - Mansor, Rozliani; Othuman Mydin, Md Azree; Ismail, Mazran; Wan Harun, Wan Mariah (Eftimie Murgu University of Resita, 2012)
Generally, there are numerous defects and problems which are common to historical building parts such as roofs, walls, floor, ceilings, toilets, door and window. Ever since the building boom of the 1970s, many of Malaysia’s historic building had been demolished. Current large scale urban development continues to threaten prewar buildings, while other historic buildings are merely declining owing to the age, abandon and high cost of maintenance. The above observation is the case with current situations found in the buildings designated in this study. Basically, it is very important to recognize and diagnose the defect that occurs at various locations with deferent types of causes and symptoms. Generally all existing structures of historical buildings are from stone, brickwork, plaster and timber. The problem, weakening and failure of the building are due to old age which gives rise to defects and faulty formation that had occurred since it was erected and aggravated by subsequent sloppy repairs or total ignorance. This paper will presents some general problems and defects occurred in historical building.